2000
DOI: 10.1080/00288306.2000.9514900
|View full text |Cite
|
Sign up to set email alerts
|

Structural setting of the Globe‐Progress and Blackwater gold mines, Reefton goldfield, New Zealand

Abstract: Globe-Progress and Blackwater mines, the two largest mines in the Reefton goldfield of North Westland, have been placed into a regional structural context dominated by upright, tight folding of the host-rock Ordovician Greenland Group turbidites. The Greenland Group lacks distinctive lithostratigraphic marker horizons or biostratigraphic control, but mapping out areas of common structural facing from the determination of bedding-cleavage vergence along two transects has revealed a series of northtrending, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Adams et al (1975) inferred that metamorphism was Silurian to Devonian, based on K-Ar dates of 438 to 395 Ma. Regional structural mapping by Rattenbury and Stewart (2000) showed that most of the gold-bearing quartz lodes are confined to a NNE-trending corridor about 5 km in width, which has shorter wavelength and tighter folds than in the adjoining areas.…”
Section: Regional Geology Of the Reefton Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Adams et al (1975) inferred that metamorphism was Silurian to Devonian, based on K-Ar dates of 438 to 395 Ma. Regional structural mapping by Rattenbury and Stewart (2000) showed that most of the gold-bearing quartz lodes are confined to a NNE-trending corridor about 5 km in width, which has shorter wavelength and tighter folds than in the adjoining areas.…”
Section: Regional Geology Of the Reefton Areamentioning
confidence: 99%
“…The wide alteration halo at Globe-Progress is interpreted to be a result of repeated deformation, including reverse and strike slip movements, along the GlobeProgress shear, a major shear zone which is markedly discordant to the northerly trending regional fold pattern (Rattenbury and Stewart 2000). This deformation has produced fracture permeability for the hydrothermal fluids to flow out from the main lodes (Christie et al 2000).…”
Section: Hydrothermal Alteration Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 cross-section C). (Grindley 1971(Grindley , 1980Laird 1972;Coleman 1977Coleman ,1981Nathan 1978;Cooper 1979b;Roder & Suggate 1990;Harrison 1993;Rattenbury & Stewart 2000).…”
Section: Buller Terrane Deformationmentioning
confidence: 99%
“…The mine was worked underground from 1876 to 1920 and was reopened as an open pit in 2007 (Christie and Brathwaite 2003;Druzbicka and Craw 2013). The host rocks are Ordovician quartz-rich clastic metasediments (Cooper 1974;Rattenbury and Stewart 2000). Greenschist facies metamorphism and associated deformation resulted in partial recrystallisation of the rocks, mainly to quartz, albite, muscovite, and chlorite.…”
Section: General Setting Of Experimental Rocksmentioning
confidence: 99%